THE EFFECT OF MASCULUS IMMERSION AGAINST THE DEATH OF MOSQUITO FLACERS - Rustam Aji; Malik Saefudin; Khambali Khambali; Ruslina Yulaika; Riang Andeko (Proceeding B-ICON, 2022)
The transition from the dry season to the rainy season causes mosquito larvae in stagnant water. Researchers are looking for natural larvicidal solutions that are safe and effective with male papaya flowers (masculus). The aim of the study was to determine the effect of masculus immersion water on the death of mosquito larvae in water reservoirs. The location is in Curup Tengah District. Quasi experimental type, Chi-square analysis, calculating odds ratio, Chi square test. Almost all (94.4%) there were 34 dead larvae and a small portion (5.5%) there were 2 live larvae, from 36 Aedes aegypti larvae in 50 ml of masculine immersion water, 1 minute. The results of Chi-square analysis showed that P value = 0.04 < ? 0.05, there was a significant effect between masculine immersion water and Aedes aegypti larvae mortality. Where the value of p value = 0.043, has the effect of masculus immersion water, at odds ratio = 4.10 times. Overall (100%) there were 36 dead larvae and a small portion (0%) there were 0 live larvae, out of 36 Aedes aegypti larvae in the bath 100 ml of masculus soaking water, time under 1 minute. The results of the Chi-square analysis showed that the P value = 0.04 <?0.05, there was a significant effect between the masculine immersion water and the mortality of Aedes aegypti larvae. Where the p value = 0.040, has the effect of masculus soaking water, at odds ratio = 4.00 times. In order for the community to be active in eradicating Aedes aegypti larvae, activities get used to making masculine soaking, pouring it into a water reservoir